Cell‐free microRNA‐148a is associated with renal allograft dysfunction: Implication for biomarker discovery - Nariman-Saleh-Fam, Ziba; Bastami, Milad; Ardalan, Mohammadreza; Sharifi, Simin; Hosseinian Khatib, Seyed Mahdi; Zununi Vahed, Sepideh (Wiley, 2019)
Chronic allograft dysfunction (CAD), the foremost cause of renal graft loss worldwide, is a serious challenge for most of the recipients. As the epigenetic era is emerging, epigenetic biomarkers especially microRNAs (miRNAs) may reflect the current stage of the disease and patient’s therapy response. The current study investigated the potential significance of circulating miRNA‐148a in predicting the renal graft function.Circulating miRNAs were isolated from 53 plasma samples of recipients with histologically validated interstitial fibrosis and tubular atrophy (IFTA, n = 26), and recipients with stable graft function (SGF, n = 27), and also healthy individuals ( n = 15). The level of miRNA‐148a was evaluated by the quantitative polymerase chain reaction (qPCR) and correlated with clinical and histological parameters.Significantly, miRNA‐148a decreased in IFTA compared with SGF subjects (P < 0.001). MiRNA‐148a levels indicated a significant association with serum creatinine levels ( r = 0.451, P = 0.021) and glomerular filtration rate ( r = −0.520, P = 0.006). MiRNA‐148a expression levels could discriminate IFTA cases from SGF individuals with an area under the curve of 0.89 ( P < 0.001), 97% sensitivity, and 72% specificity. A number of predicted targets that might be involved in CAD by miRNA‐148a were predicted.Plasma cell‐free miRNA‐148a correlated with renal function and histological grades; therefore, it may be further investigated as a novel noninvasive molecular marker of the progression to IFTA in renal transplant recipients; moreover, the emerging biomarker may become a therapeutic target in the future clinic.